Epistemic Networks on Twitter: A New Way To Learn - Gaetano Gallo; Alessandro Sturiale; Veronica De Simone; Julio Mayol (Journal of Investigative Surgery, 2021)
Introduction Surgical training results in a combination of surgical knowledge, a careful evaluation of the patients in order to choose the right operative indication and manual skills to perform the procedure, learning also how to manage any post-operative complication. Unfortunately, the level of surgical training is extremely variable being influenced by loco-regional, cultural, age-related, demographic and regulatory matters. The aim of the present study is to show the results of a recent tweetchat about surgical training. Methods: On 19 September 2018, a tweetchat about #SurgicalTraining was launched involving all the followers and the member of the recently born #SoMe4Surgery community. The tweetchat was based on ten questions (Table 1). Four of them have multiple choices while the others were open questions. Results: Between the 13th and the 23rd September 2018, there were 138 users and 837 tweets with a potential reach people of 4,603,607. There was a general agreement on the heavy impact of a dedicated mentor on the preparation of any surgical trainee. Nevertheless, exchange programs and fellowship remain among the best and fastest way of improving surgical skills. In this context, surgical societies play a leading role during the surgical training. In fact, in addition to the previously discussed opportunities, attending international conferences with dedicated trainee sessions can help to socialize with colleagues and acquiring non-technical skills. Conclusion: The professional use of social media can help to fill the gap in surgical training opening new horizons and showing the difficulties present in the world of surgery.